In Silico Analysis of Dna Profile Used in Forensic Science - SINGH SATENDRA; GAUTAM B.; YADAV P.K.; JAIN P.A.; FARMER R.; RAM G.D. (International Journal of Pharma and Bio Sciences, 2010)
Aims: The present work examined the applications of Bioinformatics in carrying out the analysis of DNA Fingerprints, which are used in the forensic sciences to investigate the crime or to establish the genetic relationship. Methods: Experiment, includes first to identify and generate DNA profile of the sample under investigation by using different techniques like RFLP analysis, PCR analysis, STR analysis, AmpFLP analysis, Y-Chromosome analysis, and Mitochondrial Analysis. Ones the DNA profile is generated different Bioinformatics tools like, BLASTP, BLASTN, ClustalW, Tagger, QTDT, GOLD, GRR, SNPtagger, PLINK, PHASE, Snphap, and different Biological Databases like GenBank, Expasy, CODIS, EDNAP and DNA databases are used to carry out analysis of DNA profile. Results: Analysis of DNA profile helps in establishing the match of the sample DNA profile under investigation with that of the standard one. If a match is found in the sample and standard one then on its bases it can be said that both belongs to the same person and absence of match indicated lack of similarity or relationship of sample with that of the standard one. Conclusions: Based on the above modern Computational and Bioinformatics tools and analysis we can address questions on forensic science like forensic examinations on defendant and prosecution positions during crime investigation and criminal court proceedings, Gender determination and Forensic entomology.